Multimodality imaging approach in the diagnosis of chronic myocarditis with preserved left ventricular ejection fraction (MCpEF): The role of 2D speckle-tracking echocardiography. (15th September 2017) - Kasner, Mario; Aleksandrov, Aleksandar; Escher, Felicitas; Al-Saadi, Nidal; Makowski, Markus; Spillmann, Frank; Genger, Martin; Schultheiss, Heinz-Peter; Kühl, Uwe; Pieske, Burkert; Morris, Daniel A.; Noutsias, Michel; et al.
Abstract: Background: Up to one third of patients with chronic myocarditis (MC) have preserved left ventricular (LV) ejection fraction (MCpEF). The purpose of this study was to evaluate the role of adding 2D speckle-tracking echocardiography (STE) to cardiac magnetic resonance imaging (cMRI) in the diagnosis of patients with MCpEF. Methods and results: We analyzed 67 patients with suspected MCpEF who underwent endomyocardial biopsy (EMB). Thirty-two patients with confirmed chronic myocardial inflammation by EMB served as study group (MCpEF) and the remaining patients ( n = 35) served as control group. In all patients, 2D STE and cMRI were performed within 48 h before EMB. Patients with MCpEF had significantly lower LV global longitudinal systolic strain (GLS) than controls (GLS: − 17.01 ± 2.42% vs. − 19.39 ± 3.81%, p < 0.001; respectively). In line, an abnormal GLS had adequate diagnostic performance to detect MCpEF (sensitivity, specificity, and accuracy of 82%, 70%, and 76%, respectively), which was superior to cMRI based on the Lake-Louise criteria (sensitivity, specificity, and accuracy 54%, 71%, and 67%, respectively). In addition, adding GLS to the Lake-Louise criteria improved significantly the diagnostic performance of cMRI to detect MCpEF (sensitivity, specificity, and accuracy 96%, 55%, and 75%, respectively). Conclusion: The findings of this study suggest that GLS using 2D STE could play an important role in the diagnostic evaluation of patients with suspected chronic myocarditis with preserved LV ejection fraction (MCpEF).